Dividing the Indivisible: Cold War Sovereignty, National Division, and the German Question at the United Nations. Issue 1 (March 2022) - Gehrig, Sebastian
Abstract: Divided Germany became one of the focal points for international disputes over sovereignty in the late 1960s and early seventies. In a period that is commonly associated with West German Ostpolitik and the diplomatic recognition of German division, the international community disputed how the sovereignty of "divided nations" should be framed under international law. The German-German battle over the terms of détente unfolded within these politics of sovereignty surrounding conflicts over "national divisions" along Cold War front lines as well as the simultaneous confrontations over postcolonial sovereignty. At the United Nations, the issues of German and Chinese division converged at the height of decolonization when East German concepts of sovereignty and self-determination challenged the UN foundational principle of "one nation, one seat" rooted in ethnic nationality. Eventually, the United Nations accepted a German exceptionalism in admitting both German states as members in 1973 based on historical rather than legal explanations for divided German sovereignty, while conflicts around "divided countries" in Asia remained unresolved. In turn, these clashes over international law transformed older German legal traditions of sovereignty and self-determination and opened up Staatsrecht frameworks to legal concepts originating from decolonization.